The visual comparison of three sequences - Hinckley, Ken; Ward, Matthew O. (Visualization, 1991. Visualization '91, Proceedings., IEEE Conference on, 1991)
A method of visual comparison is described, that provides the scientist with a unique tool to study the qualitative relationships between three sequences of numbers or symbols. The program displays a 3D shape containing the sequence similarities and differences, which manifest themselves as simple geometric shapes and colors that a human observer can easily detect and classify. The method presents all possible correlations to the user, giving it a considerable advantage over existing sequence comparison tools that only search for a programmed subset of all possible correlations. Thus, using this technique, researchers may detect sequence similarities that other analytic methods might completely overlook. The program can also filter out undesirable or insignificant correlations. The technique is easily adapted to a wide range of applications.